2003
DOI: 10.1038/sj.gene.6363985
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants of the IL13 and IL4 genes and atopic diseases in at-risk children

Abstract: We studied a cohort containing 368 children at high risk of developing atopy and atopic disorders and 540 parents of those children to investigate whether the IL13 Arg130Gln and CÀ1112 T polymorphisms were associated with these outcomes. We also investigated whether haplotypes consisting of any two polymorphisms of IL13 Arg130Gln, IL13 CÀ1112 T and IL4 CÀ589 T were associated with these phenotypes. In 288 white children, the IL13 130Gln allele was associated with atopy (RR ¼ 1.9, P ¼ 0.047), and with atopic de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(73 citation statements)
references
References 43 publications
(67 reference statements)
3
63
1
5
Order By: Relevance
“…IL13 and VDR have been previously examined in the CAPPS (He et al 2003) (IL13) and SLSJ (Poon et al 2004) (VDR) panels. A sensitivity analysis was conducted by excluding the CAPPS cohort from the IL13 combined analysis with a small change in the adjusted P value for asthma rs2243204 (P = 0.0126 to P = 0.0328), rs20541 (P = 0.0342 to P = 0.08016), and rs1295686 (P = 0.0424 to P = 0.11406).…”
Section: Combined Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…IL13 and VDR have been previously examined in the CAPPS (He et al 2003) (IL13) and SLSJ (Poon et al 2004) (VDR) panels. A sensitivity analysis was conducted by excluding the CAPPS cohort from the IL13 combined analysis with a small change in the adjusted P value for asthma rs2243204 (P = 0.0126 to P = 0.0328), rs20541 (P = 0.0342 to P = 0.08016), and rs1295686 (P = 0.0424 to P = 0.11406).…”
Section: Combined Resultsmentioning
confidence: 99%
“…The individual panels include (1) the Canadian Asthma Primary Prevention Study (CAPPS) cohort (Becker et al , 2004Chan-Yeung et al 1999, 2000, 2005He et al 2003;Hegele et al 2001;Kaan et al 2000), which is comprised of 549 children from 545 families at high risk for developing asthma and their parents and is predominantly C. Laprise Département des sciences fondamentales, Université du Québec à Chicoutimi, Saguenay, Quebec, Canada C. Laprise Université de Montréal Community Genomic Medicine Center, Chicoutimi Hospital, Saguenay, Quebec, Canada n/a 31 n/a n/a n/a 31 Atopy 18 44 n/a 62 n/a n/a n/a 62 AHR 14 22 n/a 36 n/a n/a n/a 36…”
Section: Study Samples (Panels)mentioning
confidence: 99%
“…Consistent with the prominent role of IL-13 in experimental asthma, robust associations have been detected between IL13 polymorphisms and allergic phenotypes. IL13+2044G→A is strongly associated with increased total serum IgE (22)(23)(24)(25), asthma (26), atopy (27), atopic dermatitis (23,27,28), and a grouped phenotype that includes eosinophilia, IgE, and positive skin tests (29). IL13-1112C→T is associated with asthma, bronchial hyperreactivity and skin test responsiveness (30,31), total IgE (32), and sensitization to food and outdoor allergens (32,33).…”
mentioning
confidence: 99%
“…Of the genetic association studies conducted in countries other than Japan, to our knowledge, only 1 case-control study of Danish subjects aged 17-66 years found a significant relationship between SNP rs1800925 and atopic eczema [9]. In contrast, a null association between SNP rs1800925 and eczema was observed in studies of Canadian [10], US [11], and UK [13] children as well as in a study of children aged 8-12 years from 13 countries [14] and a study of Taiwanese young adults [12]. Two studies of German [7] and Canadian [10] children found a significant association between SNP rs20541 and eczema, whereas a relationship between SNP rs20541 and eczema was ruled out in 2 studies of US [11] and UK [13] children and in a study of Taiwanese adults [12].…”
Section: Discussionmentioning
confidence: 99%